STUDI KINERJA ALGORITMA LOAD BALANCING STATIS PADA INFRASTRUKTUR HOMOGEN TERHADAP APLIKASI WEB MICROSERVICES - Alysha Namora Putri Harahap; Galura Muhammad Suranegara (LPPM Universitas Abdurrab, 2026)
Technological developments have led to the emergence of cloud computing as a solution to improve system reliability and scalability. One of its components, load balancer, plays an important role in distributing the workload to keep the system optimal, so choosing a load balancing algorithm is a crucial step. This study tested several static load balancing algorithms in a homogeneous server environment based on microservices architecture on two cloud platforms, namely AWS and GCP. With the current experimental design, the tests showed that no algorithm consistently excelled in all scenarios, while AWS tended to display more stable performance than GCP. These results can serve as a basis for further research exploring variations in configuration, load scenarios, or larger system scales to evaluate algorithm and platform performance more comprehensively.